Characterization of Activated Carbon from Coal and Its Application as Adsorbent on Mine Acid Water Treatment - Siti Hardianti; Susila Arita Rachman; Harminuke E.H. (IJFAC (Indonesian Journal of Fundamental and Applied Chemistry), 2017)
Anthracite and Sub-bituminous as activated carbon raw material had been utilized especially in mining field as adsorbent of dangerous heavy metal compound resulted in mining activity. Carbon from coal was activated physically and chemically in various temperature and particle sizes. Characterization was carried out in order to determine the adsorbent specification produced hence can be used and applied accordingly. Proximate and ultimate analysis concluded anthracite has fixed carbon 88.91% while sub-bituminous 49.05%. NaOH was used in chemical activation while heated at 400-500°C whereas physical activation was conducted at 800-1000°C. Activated carbon has high activity in adsorbing indicated by high iodine number resulted from analysis. SEM-EDS result confirmed that activated carbon made from coal has the quality in accordance to SNI and can be used as adsorbent in acid water treatment.